The Effectiveness of the E-Book-Assisted Inquiry and Discovery Learning Model on the Critical Thinking - Astutik `Astutik; Joko Siswanto; Aryo Andri Nugroho (Journal La Edusci, 2026)
This study aims to determine the effectiveness of the Inquiry and Discovery Learning learning models assisted by e-books on the critical thinking skills of fifth-grade elementary school students. This study uses a quantitative approach with a quasi-experimental design in the form of a pretest-posttest control group design. The research subjects consisted of three groups, namely the class using the Inquiry model, the class using the Discovery Learning model, and the control class using conventional learning. Data collection techniques were carried out through critical thinking ability tests. Data were analyzed using normality tests, homogeneity tests, and hypothesis testing using ANOVA. The results showed that the data were normally distributed and homogeneous. Hypothesis testing showed significant differences between the three groups, with a significance value <0.05. The Inquiry learning model has a higher effectiveness than Discovery Learning, but both models are proven to be more effective than conventional learning in improving students' critical thinking skills. The use of e-books as a learning medium also makes a positive contribution in increasing student motivation and involvement in the learning process. Based on the results of the study, it can be concluded that the Inquiry and Discovery Learning learning models assisted by e-books are effective in improving elementary school students' critical thinking skills. Therefore, teachers are advised to implement innovative learning models supported by technology to improve the quality of learning.